The state of harm reduction in prisons in 30 European countries with a focus on people who inject drugs and infectious diseases - Heino Stöver; Anna Tarján; Gergely Horváth; Linda Montanari (BMC, 2021)
Abstract Background People who inject drugs are often imprisoned, which is associated with increased levels of health risks including overdose and infectious diseases transmission, affecting not only people in prison but also the communities to which they return. This paper aims to give an up-to-date overview on availability, coverage and policy framework of prison-based harm reduction interventions in Europe. Methods Available data on selected harm reduction responses in prisons were compiled from international standardised data sources and combined with a questionnaire survey among 30 National Focal Points of the European Monitoring Centre for Drugs and Drug Addiction to determine the level of availability, estimated coverage and policy framework of the interventions. Results Information about responses to health harms in prisons is limited and heterogeneous. Cross-country comparability is hampered by diverging national data collection methods. Opioid substitution treatment (OST) is available in 29 countries, but coverage remains low (below 30% of people in need) in half of the responding countries. Needle and syringe programmes, lubricant distribution, counselling on safer injecting and tattooing/piercing are scarcely available. Testing for infectious diseases is offered but mostly upon prison entry, and uptake remains low in about half of the countries. While treatment of infections is mostly available and coverage is high for human immunodeficiency virus (HIV) and tuberculosis, hepatitis B and C treatment are less often provided. Health education as well as condom distribution is usually available, but provision remains low in nearly half of the countries. Post-release linkage to addiction care as well as to treatment of infections is available in a majority of countries, but implementation is often partial. Interventions recommended to be provided upon release, such as OST initiation, take-home naloxone and testing of infections, are rarely provided. While 21 countries address harm reduction in prison in national strategic documents, upon-release interventions appear only in 12. Conclusions Availability and coverage of harm reduction interventions in European prisons are limited, compared to the community. There is a gap between international recommendations and 'on-paper' availability of interventions and their actual implementation. Scaling up harm reduction in prison and throughcare can achieve important individual and public-health benefits.